Effect of weightlifting training on jumping ability, sprinting performance and squat strength: A systematic review and meta-analysis - García-Valverde, A.; Manresa-Rocamora, A.; Hernández-Davó, J. L.; Sabido, R. (International Journal of Sports Science & Coaching, 2022)
This systematic review and meta-analysis aimed to assess the effect of using weightlifting movement and their derivatives in training on vertical jump, sprint times, and maximal strength performance. Thirty-four studies were used for meta-analysis with a moderate quality on the PEDro scale. Meta-analysis showed positive effects of weightlifting training, especially when combined with traditional resistance training on countermovement jump performance, sprint times, and one-repetition maximum squat (ES = 0.41, ES = -0.44, and ES = 0.81, respectively). In conclusion, results revealed the usefulness of weightlifting combined with traditional resistance training in improving sprint, countermovement jump and maximal strength performance.